Relationships between measures of adiposity with subclinical atherosclerosis in patients with type 2 diabetes. Issue 8 (29th June 2016) - Yuan, Mingxia; Hsu, Fang‐Chi; Bowden, Donald W.; Xu, Jianzhao; Carrie Smith, S.; Wagenknecht, Lynne E.; Comeau, Mary E.; Divers, Jasmin; Register, Thomas C.; Jeffrey Carr, J.; Langefeld, Carl D.; Freedman, Barry I.
Abstract : Objective: Assess cross‐sectional relationships between body mass index (BMI), waist circumference (WC), pericardial (PAT), visceral (VAT), and subcutaneous adipose tissue (SAT) volumes with calcified plaque (CP) in African Americans (AAs) and European Americans (EAs) with type 2 diabetes. Methods: Computed tomography measured PAT, VAT, SAT, and CP in coronary arteries (CAC), carotid arteries, and aorta. Generalized estimating equations models were fitted to test for associations between adiposity and CP, stratified by ethnicity while accounting for familial correlations. Results: AAs ( N = 753) vs. EAs ( N = 562) had significantly lower PAT and VAT, despite equal or higher BMI. In multivariable models adjusting for age, gender, education, HbA1c, statins, smoking, cardiovascular disease, hypertension, nephropathy, and C‐reactive protein, PAT positively associated with presence of CAC in AAs ( P < 0.001), not EAs ( P = 0.68; ethnicity interaction P < 0.01). Inverse associations were detected between SAT and severity of aorta CP ( P < 0.01) in AAs and between BMI, WC, and SAT with severity of aorta CP in all participants. Conclusions: Ethnic‐ and gender‐specific differences in BMI, WC, PAT, SAT, and VAT were present in AAs and EAs with diabetes. Only PAT was positively associated with CAC in AAs; paradoxical inverse associations were seen between several other adiposity measures and subclinical cardiovascular disease.